The Rāsa Māna ke Pada of Kevalarāma : A Medieval Hindi Text of the Eighth Gaddī of the Vallabha Sect - Entwistle, Alan W. (Asian Studies - Book Archive pre-2000, 1993)
This book of the well-known Braj specialist, Prof Dr A.W. Entwistle (University of Washington), focuses on the medieval tradition of the eighth branch of the Vallabha sect. The lengthy introduction deals with the sectarian background of the branch, including a survey of the relevant tradition and history of medieval Vaiṣṇava devotion as a whole and the Vallabha sect in particular. It discusses the structure of the Puṣṭimārga and its gaddīs, or branches, since Rāsa Māna ke Pada is part of the literary heritage of the sect's Eighth Gaddī which, until partition in 1947, was based at Dera Ghazi Khan (now in Pakistan). It gives a , survey of the life and works of the founders of this gaddī, ŚrI Lālajī, and of his grandson Kevalarāma. Due attention is also paid to the language of the text and in an appendix a comparative etymological glossary is given that cites examples from other Braj Bhāṣā authors in order to support interpretations of the more obscure words and idioms. The main part of the book consists of a critical edition of the Rāsa Māna ke Pada , a collection of poems attributed to Kevalarāma, and an annotated translation into English.